Residential proximity to major roadways and risk of incident ischemic stroke in the Northern Manhattan Study - Kulick, Erin R. (Stroke, 2018)
BACKGROUND AND PURPOSE: The evidence supporting the deleterious cardiovascular health effects of living near a major roadway is growing, although this association is not universal. In primary analyses, we hypothesized that residential proximity to a major roadway would be associated with incident ischemic stroke, and that cardiovascular risk factors would modify that association. METHODS: The Northern Manhattan Study (NOMAS) is an ongoing, population-based cohort study designed to measure cardiovascular risk factors, stroke incidence, and other outcomes in a multiethnic urban population. Recruitment occurred from 1993–2001 and participants are followed-up annually by telephone. Residential addresses at baseline were geocoded and Euclidean distance to nearest major roadway was estimated and categorized as in prior studies. We used Cox proportional hazard models to calculate hazard ratios (HRs) and 95% confidence intervals (95%CIs) for the association of this distance to incidence of stroke and other outcomes, adjusting for sociodemographic and cardiovascular risk factors, year at baseline, and neighborhood socioeconomic status. We assessed whether these associations varied by age, sex, smoking status, diabetes, and hypertension. RESULTS: During a median follow-up period of 15 years (n=3,287), 11% of participants were diagnosed with ischemic stroke. Participants living <100m from a roadway had a 42% (95%CI 1.01–2.02) higher rate of ischemic stroke versus those living >400m away. This association was more pronounced among non-current smokers (HR 1.54; 95%CI 1.05–2.26) and not evident among smokers (HR 0.69; 95%CI 0.23–2.06). There was no clear pattern of association between proximity to major roadways and other cardiovascular events including myocardial infarction, all-cause death, or vascular death. CONCLUSIONS: In this urban multiethnic cohort we found evidence supporting that within-city variation in residential proximity to major roadway is associated with higher risk of ischemic stroke. An individual’s smoking history modified this association, with the association remaining only among participants not currently smokers.